2011
DOI: 10.19030/jber.v9i1.947
|View full text |Cite
|
Sign up to set email alerts
|

Getting Proactive: Cultural And Procedural Drivers Of Managerial Motivation To Act

Abstract: <p class="MsoNormal" style="text-align: justify; text-indent: 0in; margin: 0in 19.35pt 0pt 0.5in;"><span style="mso-bidi-font-size: 10.0pt;"><span style="font-size: x-small;"><span style="font-family: Times New Roman;">The importance of managers&rsquo; proactive behaviors in the workplace is well documented. While previous studies have focused on dispositional drivers of proactive behaviors, this paper investigates situational - cultural and procedural - factors that affect managers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The scientists also prove in their studies that intrinsic motivation is manifested through normative motivation (inclines towards the idea that technology allows to obtain a number of external benefits, namely fulfillment of tasks, increasing the level of labor productivity and hedonic motivation providing the pleasure of using technologies (Ke et al, 2012). Rusetski (2011) has examined the cultural and procedural factors that influence the motivation of business executives. The study has found that an important factor that reduces the level of manager's motivation is the strategic orientation of technologies.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The scientists also prove in their studies that intrinsic motivation is manifested through normative motivation (inclines towards the idea that technology allows to obtain a number of external benefits, namely fulfillment of tasks, increasing the level of labor productivity and hedonic motivation providing the pleasure of using technologies (Ke et al, 2012). Rusetski (2011) has examined the cultural and procedural factors that influence the motivation of business executives. The study has found that an important factor that reduces the level of manager's motivation is the strategic orientation of technologies.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…However, customer orientation of the enterprise and cultural disregard of the classical management principles only increase the motivation of managers. According to the scientist's conclusion, the influence of cultural factors remains more effective in motivating managers than carrying out an appropriate assessment of the manager's activities or providing him with compensatory payment (Rusetski, 2011).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Furthermore, motivation is commonly sourced from intrinsic or extrinsic motives, where intrinsic motivation involves people doing an activity because they find it interesting, and derive spontaneous satisfaction from the activity itself, while extrinsic motivation, in contrast, requires an instrumentality between the activity and some separable consequences such as tangible or verbal rewards; hence, satisfaction comes not from the activity itself but rather from the extrinsic consequences to which the activity leads, to enhance motivation in a company. Rusetski (2011) asserts that; employers need to make an effort to understand and guide their workers in achieving the organizational goals or targets, in order to be effective in handling their project team or their subordinates. They should have an understanding of motivational forces as well as taking seriously the responsibility to create a happy work environment for the employees.…”
Section: G Motivationmentioning
confidence: 99%
“…It also referred to as the ability of the firm to utilize its technical knowledge to build a new technical solution to satisfy the needs and wants of the market (Gatignon & Xuereb, 1997;Spanjol, Qualls, & Rosa, 2011). Rusetski (2011) conceptualizes technology orientation as the ability and willingness of business firms to obtain technical knowledge and use it to improve product development.…”
Section: Literature Reviewmentioning
confidence: 99%